IMPROVING STUDENT LEARNING OUTCOMES SDN PULOREJO THROUGH TEAM ACCELERATED LEARN USING DIORAMA MEDIA - Nadia Ayu Martasari; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The implementation of learning the teacher does not use diverse learning models for students, so that student learning motivation decreases. This often happens, especially in science learning which is often said to be difficult by students because it is boring and tends to be boring due to the large amount of abstract material. This study aims to improve science learning outcomes for fifth grade students at SDN Pulorejo Jombang by applying the Team Accelerated Instruction learning model. The type of research used is Classroom Action Research using the model from Kemmis and MC Taggart, which applies two cycles in its implementation. Each cycle includes 4 stages, namely: the planning stage, the implementation stage, the observation stage, and the reflection stage. In this study, the subjects were the fifth grade students of SDN Pulorejo, amounting to 25 people. The techniques used in collecting data are observation, tests, interviews, documentation, etc. While the data analysis technique used quantitative and qualitative analysis.. After carrying out research activities in two cycles, the results obtained are an increase in science learning outcomes for fifth grade students at SDN Pulorejo Jombang by applying the Team Accelerated Instruction learning model.